2009
DOI: 10.1097/qai.0b013e3181945f03
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing Frequency Among Men Who Have Sex With Men Attending Sexually Transmitted Disease Clinics: Implications for HIV Prevention and Surveillance

Abstract: In MSM seen at 4 STD clinics, the percentage of never previously HIV tested is decreasing and MSM are testing more frequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 26 publications
3
70
1
1
Order By: Relevance
“…For example, the positivity rate (number of HIV-positive tests divided by number of tests conducted) for firsttime tests (4.1%) was similar to repeat tests (3.7%). These rates are consistent with positivity rates (3.8%) reported among MSM testing through STD clinics (Helms et al, 2009). Additionally, testing and positivity levels were most prevalent among 20-to 29-year-olds and less prevalent in older age groups, for both first-time and repeat test groups.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…For example, the positivity rate (number of HIV-positive tests divided by number of tests conducted) for firsttime tests (4.1%) was similar to repeat tests (3.7%). These rates are consistent with positivity rates (3.8%) reported among MSM testing through STD clinics (Helms et al, 2009). Additionally, testing and positivity levels were most prevalent among 20-to 29-year-olds and less prevalent in older age groups, for both first-time and repeat test groups.…”
Section: Discussionsupporting
confidence: 79%
“…There is evidence that most MSM are repeat or regular testers (Fernyak et al, 2002;Helms et al, 2009;Lauby & Milnamow, 2009), indicating frequent opportunities to engage in client-centered risk counseling and be exposed to HIV prevention messages. However, some studies have indicated that MSM who test repeatedly have higher levels of risky sexual and drug-use behavior and greater HIV prevalence than MSM who have tested only once (Fernyak et al, 2002;MacKellar et al, 2002;Sifakis et al, 2007).…”
mentioning
confidence: 99%
“…Gonorrhoea and chlamydia were found in 26% and 19%, respectively, among newly HIVdiagnosed MSM in San Francisco [100]. Concurrent chlamydia, Gonorrhoea and syphilis were significant predictors of new HIV in four US metropolitan areas 2002-2006 [101]. Ano-rectal Gonorrhoea is an independent risk factor for HIV seroconversion [102] and high rates of new HIV infections have been observed after ano-rectal Gonorrhoea [98].…”
Section: Hivmentioning
confidence: 99%
“…Adherence to this recommendation also became the object of analysis 31,35,36,42 . While repeat testing had initially raised concern, in this new context the "problem" became those who had not tested in the previous year (e.g., Katz et al 38 , Knussen et al 35 ).…”
Section: Recent Test As An Indicator Of Current Individual Carementioning
confidence: 99%